Maternal high-fat diet acts as a stressor increasing maternal glucocorticoids' signaling to the fetus and disrupting maternal behavior and brain activation in C57BL/6J mice. (October 2015) - Bellisario, Veronica; Panetta, Pamela; Balsevich, Georgia; Baumann, Valentin; Noble, June; Raggi, Carla; Nathan, Olivia; Berry, Alessandra; Seckl, Jonathan; Schmidt, Mathias; Holmes, Megan; Cirulli, Francesca
Highlights: HFD mediates an imbalance in the expression of the genes that regulate the time window of fetal exposure to maternal glucocorticoids. HFD disrupts behavior of the dam both before and after parturition. HFD reduces neural activity in brain regions involved in olfactory processing and social recognition. HFD feeding is a stressful challenge during pregnancy with relevant consequences on fetal development. Summary: Maternal diet during pregnancy can impact maternal behavior as well as the intrauterine environment, playing a critical role in programming offspring's physiology. In a preliminary study, we found a strong association between high-fat diet (HFD) during pregnancy and increased cannibalistic episodes and dams' mortality during late pregnancy and parturition. Based upon these data, we hypothesized that HFD during pregnancy could negatively affect neuroendocrine and metabolic regulations occurring during the final stages of pregnancy, thereby disrupting maternal behavior. To test this hypothesis, female C57BL/6J mice were fed HFD or control diet for 11 weeks until three days before the expected delivery date. Basal corticosterone plasma levels and brain levels of c-Fos were measured both before and after delivery, in addition to leptin levels in the adipose tissue. Dam's emotional behavior and social anxiety, in addition to locomotor activity were assessed before parturition. Data show that HFD led to aberrant maternal behavior, dams being characterized by behaviors related to aggression toward an unfamiliar social stimulus in the social avoidance test, in addition to decreased locomotor activity. Neural activity in HFD dams was reduced in the olfactory bulbs, a crucial brain region for social and olfactory recognition hence essential for maternal behavior. Furthermore, HFD feeding resulted in increased circulating levels of maternal corticosterone and decreased levels of leptin. In addition, the activity of the protective 11β-dehydrogenase-2 (11β-HSD-2) barrier in the placenta was decreased together with 11β-dehydrogenase-1 ( 11β-HSD-1 ) gene expression. Overall, these data suggest that HFD acts as a stressful challenge during pregnancy, impairing the neuroendocrine system and the neural activity of brain regions involved in the processing of relevant olfactory stimuli, with negative consequences on maternal physiology and behavior.